AN ANALYSIS OF STUDENT’S RESILIENCE IN ONLINE ENGLISH CLASS DURING PANDEMIC ERA AT ENGLISH STUDY PROGRAM UNIVERSITAS MUHAMMADIYAH BENGKULU - Fadillah, Putri; Achmad Nurcholis, Ivan (Pusat Riset dan Inovasi Nasional, 2022)
The COVID-19 pandemic has changed the way universities learn. Teaching and learning activities that usually take place face-to-face have evolved into virtual meetings in various online learning applications. This paper aims to analyze the resilience of students in handling online English courses from a perspective or from the perspective of coping with online learning challenges during the COVID-19 pandemic. This document collects 20 students who are actively participating in online learning activities as an example for the